Kritik terhadap Hadis-hadis Misoginis dalam Pendekatan Trans Queer - Hidayah, Nur (El Nubuwwah Jurnal Studi Hadis, 2024)
This study examines a critique of a misogynistic hadith that states a woman can invalidate a person's prayer. The approach adopted is trans-queer theory, which seeks to deconstruct gender-based discrimination within Islamic discourse. Misogynistic hadiths have often been used as a justification for systemic gender discrimination, reinforcing social and domestic inequalities. One particular hadith under scrutiny claims that a person’s prayer is disrupted if a woman, a donkey, or a dog passes in front of them. Such interpretations have historically contributed to the marginalization of women in religious and social contexts. This research employs a qualitative methodology with a library research approach, collecting data from classical Islamic texts, books, peer-reviewed journals, and other scholarly works. Through critical textual analysis, findings reveal that the hadith in question must be re-examined within its historical and socio-cultural context, preventing its misuse as a basis for gender discrimination in religious practice. The study affirms that women neither invalidate prayers nor hold an inferior status, as often misinterpreted. By incorporating trans-queer perspectives, this study challenges traditional patriarchal readings and advocates for a more inclusive and just understanding of hadith. Ultimately, this research contributes to the ongoing discourse on gender justice in Islam, fostering a more equitable and non-discriminatory social and religious environment.